Effects of alkaline versus mineral water on endurance performance in trained cyclists - Hottenrott, K.; Ketelhut, S.; Rabe, J.; Zurleit, A. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Water provides a performance-limiting factor during exercise. Besides quantity and time of consumption, quality and composition are important. It has been shown that alkaline supplementation (AS) can prevent a decrease in blood HCO3- during high intensity exerise (Pouzash et al., 2012). Therefore AS with hydrogen carbonate may increase endurance capacity (EC). The aim of the study was to evaluate the influence of natural alkaline glacier water (AGW) and commercially available mineral water (MW) on aerobic and anaerobic EC. Methods: The quasi-experimental study involved 7 female and 11 male cyclists (mean age 26.4 ± 4.8 yr, BMI 23.1 ± 2, 6 kg/m^2) that engaged in 7.2 ± 2.6 hours of physical activity per week. Subjects displayed a mean VO2max of 56.9 ± 7.8 ml/min/kg in male, and 42.4 ± 2.4 ml/min/kg in female. Using a controlled, blinded cross-over design subjects were randomized in two groups. Time-toexhaustion-test (TET) at 80% of individual VO2max and anaerobic 75-s-cycling test (A75) at 90 R/min were conducted with a 20 minute recovery in between. Test protocol was repeated after 7 days. Three days before each test protocol athletes consumed 3 liters of MW or AGW every day. On test days, athletes drank another liter of MW or AGW one hour before and a pint in between the two tests. The diet in the days before was controlled and standardized with respect to the liquid supply. Statistical analysis was performed using SPSS 20.0. The significance level was set to p 0.05. Results: Cyclists consuming AGW scored a significant (p < .01) longer travel time in the TET than cyclists consuming MW (47.4 ± 6.7 min versus 43.4 ± 9.3; 8.4%). After the test, oxygen uptake in the intervention with AGW was significantly higher (p = .027) than in the intervention with MW (46.8 ml/min/kg versus 44.9 ml/min/kg. During A75 subjects drinking AGW achieved a significant higher (p < .01, 8.2%) output (446.6 ± 164.9 watts) compared to subjects drinking MW (410.0 ± 128.8 watts). Discussion: Milieu shifts are an important limiting factor in endurance performance (Heil, et al., 2012). During intense physical stress the blood pH can fall below 7.0, decreasing the oxygen binding properties. Various buffer systems can influence the pH value (Pilegaard et al., 1999) effecting the acid-base balance. In this context it has been shown, that alkaloids can increase the blood buffer capacity and therefore improve EC (Nielsen et al., 2002). An improved buffering capacity and oxygen-binding capacity through AGW may have contributed to the improved performance in the cycling test, highlighting the performance enhancing effects induced by a natural product from the glaciers.